Epidemiology of proximal femur fractures in the young population of Qatar - Ashraf T. Hantouly (14150319) (2023)
Purpose To review the epidemiological characteristics of proximal femur fractures in the young population (< 60 years) of Qatar between 2017 and 2019. Methods All patient treated for proximal femur fractures at Hamad General Hospital (HGH), a level one trauma center, were retrospectively reviewed between Jan 2017 and Dec 2019. All adults (18–60 years) with proximal femur fracture (femur head, femur neck, intertrochanteric and subtrochanteric fractures) were included with no restriction to the AO/OTA classification or fractures subtypes. Excluded cases were pathological fractures, cases with insufficient documentation or no radiographs. Results A total of 203 patients with a mean age of 40.07 ± 11.76 years were included, of who 89.9% were males. The incidence of proximal femur fracture was 3.12/100,000/year. Fall from height (48.1%) followed by road traffic accidents (26.9%) were common cause of injury. The most common fracture type was intertrochanteric fracture (36.1%) followed by femur neck fractures (33.7%). Conclusion This study provides the initial insights into the proximal femur fractures in the young population of Qatar. This is the first study to investigate of the epidemiology of such fractures in this particular patient group. Contrary to the existing literature on older age groups, the majority of the injuries were observed in males. Falls from height followed by road traffic accidents were the primary mechanisms leading to these fractures. Improved understanding of the profile of these injuries can aid in their prevention by implementing more effective safety measures. Other Information Published in: European Journal of Orthopaedic Surgery & Traumatology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00590-023-03664-1 Additional institutions affiliated with: Surgical Specialty Center - Hamad General Hospital